(untitled) - Dizard, Wilson P. (New York, 1984)
This text has been revised and updated and includes the events, changes and developments in technology, economics, and politics since the second edition appeared. It describes the high technology equipment that is leading the revolution in communication; shows how the information age will supplant the age of industrialization; and outlines the economic and social opportunities - as well as the pitfalls - that are inherent in this revolution. In particular, it brings the subject up-to-date into the 1990s - incorporating important developments in technology, economics, and politics. It examines the next generation of "smart computers"; the introduction of high definition television and the growth of specialized electronic networks. It also investigates the role of the Federal government in deregulating American telecommunications and in reducing international trade barriers for American communications and information firms.
Keywords: Communication; United states